2019
DOI: 10.1101/541417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The landscape of the alternatively spliced transcriptome remains stable during aging across different species and tissues

Abstract: Aging is characterized by a decline of cellular homeostasis over time, leading to various severe disorders and death. Alternative splicing is an important regulatory level of gene expression and thus takes on a key role in the maintenance of accurate cell and tissue function. Missplicing of certain genes has already been linked to several age-associated diseases, such as progeria, Alzheimer's disease, Parkinson's disease and cancer. Nevertheless, many studies focus only on transcriptional variations of single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 75 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…The resulting studies in human have supported the initial age‐related splicing changes found in mouse and rat. As with the SF expression studies, experiments in humans and mice both support the hypothesis that changes in AS patterns occur with age—though individual AS events may be species‐specific (Sieber et al, 2019) or not obviously conserved between species. In the following paragraphs, we will highlight the several studies that have identified age‐related AS changes.…”
Section: Age‐related Alterations In Spliced Isoformsmentioning
confidence: 67%
See 1 more Smart Citation
“…The resulting studies in human have supported the initial age‐related splicing changes found in mouse and rat. As with the SF expression studies, experiments in humans and mice both support the hypothesis that changes in AS patterns occur with age—though individual AS events may be species‐specific (Sieber et al, 2019) or not obviously conserved between species. In the following paragraphs, we will highlight the several studies that have identified age‐related AS changes.…”
Section: Age‐related Alterations In Spliced Isoformsmentioning
confidence: 67%
“…Gene ontology, pathway, and network analysis of age‐related spliced transcripts across all five tissues highlighted pathways associated with posttranscriptional RNA processing, spliceosome, EIF2 translational control, and cancer (Rodriguez et al, 2016). Finally, a cross‐species comparative analysis comparing AS changes in blood, brain, liver, and skin in young versus older humans, mice, and two fish species, revealed that overall less than 5% of transcribed genes are differentially spliced during aging (Sieber et al, 2019). Although most of the age‐related differentially spliced transcripts are tissue‐ and species‐specific, several spliced transcripts shared across tissues and species were associated with RNA processing, including splicing and translational control (Sieber et al, 2019).…”
Section: Age‐related Alterations In Spliced Isoformsmentioning
confidence: 99%
“…However, little is known on the global change between the most abundant isoforms of a gene in different tissues over time. A few studies identified individual isoforms derived from AS to be robust with age [ 167 , 168 ]. Lin et al [ 168 ] discovered that the expression of one isoform of insulin-like growth factor-I (IGF-I), an important age regulator, is downregulated during aging in mice, while another one has a constant expression.…”
Section: Regulatory and Molecular Aspectsmentioning
confidence: 99%
“…Huan et al point out that small proportions of AS change over time and are associated with age in different human tissues [ 171 ]. In a recent bioinformatics study, we found that AS is robust to aging for the majority of genes across various species, notably humans, mouse, zebrafish ( Danio rerio ), and killifish ( Nothobranchius furzeri ) as well as across different tissues [ 167 ]. This observation indicates that the whole splicing process seems to stay robust during aging.…”
Section: Regulatory and Molecular Aspectsmentioning
confidence: 99%
See 1 more Smart Citation